2004
DOI: 10.1002/app.13644
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of physicochemically treated LDPE by a consortium of filamentous fungi

Abstract: Samples of low density polyethylene previously subjected to physicochemical treatments-thermal treatment (TT) at 105 and 150°C or accelerated aging treatment (AAT)-were subjected to biodegradation by a consortium of four fungi during 9 months. Morphological, structural, and surface changes and mineralization were evaluated. TT samples showed decreases in the onset melting temperature (T o ), melting point (T m ), relative crystallinity (⌽), and mean crystallite size (L 110 ). The degradation products in all tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 20 publications
7
49
0
4
Order By: Relevance
“…The biodegradation rate obtained in the present study is in agreement with the earlier reports ranging from 3.5 to 8.4% for polyethylene incubated in soil for 10 years (Albertsson and Karlsson 1990). This decrease in weight is in association to the others' findings (Singh et al (2012), Gilan et al (2004), Manzur et al (2004), Salleh et al (1993)) carried out degradation of LDPE using Aspergillus fumigatus and Penicillium sp. According to their work, A. fumigatus was able to degrade 4.65% of polyethylene and Penicillium sp.…”
Section: Reduction In Weight Measurement Of Ldpe Filmssupporting
confidence: 93%
See 1 more Smart Citation
“…The biodegradation rate obtained in the present study is in agreement with the earlier reports ranging from 3.5 to 8.4% for polyethylene incubated in soil for 10 years (Albertsson and Karlsson 1990). This decrease in weight is in association to the others' findings (Singh et al (2012), Gilan et al (2004), Manzur et al (2004), Salleh et al (1993)) carried out degradation of LDPE using Aspergillus fumigatus and Penicillium sp. According to their work, A. fumigatus was able to degrade 4.65% of polyethylene and Penicillium sp.…”
Section: Reduction In Weight Measurement Of Ldpe Filmssupporting
confidence: 93%
“…Microorganisms colonize the polymer surface and adhere by extracellular polymer production. The results obtained are in close association with earlier reports (Manzur et al 2004;Volke-Sepulveda et al 2002). This change in growth rate could be a cellular response to the change in surface topography of the LDPE film during degradation whereby pits are formed on the film surface due to enzymatic digestion.…”
Section: Surface Morphology Study Of Ldpesupporting
confidence: 91%
“…Furthermore, it was found that this decrease in the crystalline content occurs concurrently with a slight increase in the maximum lamellar thickness (Tables 4, 5), suggesting that once biodegradation proceeds, thinner crystalline entities are firstly being affected. Manzur et al reported similar results for physico-chemically aged LDPE films submitted to biodegradation by a fungi consortium [71].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 63%
“…Although oxygen is usually insoluble in the crystalline phase and biodegradation cannot be expected to be initiated in this phase, changes occurring in the amorphous phase due to the degradation process, are likely to also subsequently affect the crystalline phase [67]. This could explain the further slight decrease in crystallinity [70,71]. Furthermore, it was found that this decrease in the crystalline content occurs concurrently with a slight increase in the maximum lamellar thickness (Tables 4, 5), suggesting that once biodegradation proceeds, thinner crystalline entities are firstly being affected.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[19] Polyethylene Brevibacillus borstelensis [36] Rhodococcus rubber [37] Penicillium simplicissimum YK [9] Brevibacillus borstelen [38] Penicillium frequentans Bacillus mycoides [10] Aspergillus niger Penicillium pinophilium [11] Penicillium pinophilium Aspergillus niger Cliocladium virens Penicillium chrysosporium [12] Bacillus sphericus Bacillus cereus [13] Streptomyces spp. • 생물적 요인: 세포 외 효소분비, 소수성 표면으로의 부착 정도, 바이오 계면활성제 등.…”
Section: 미생물에 의해 이루어진다 플라스틱으로 사용되는 다양한 고분자들은 분자량이 크기 때문에 용해도가 낮고 미생unclassified